On the place code for pitch: A psychophysiological paradox in the classical concept - Jozef J. ZWISLOCKI (Archives of Acoustics, 2014)
The place of maximum excitation in the cochlea has been believed to be the code for the pitch of tones since mid 19-th century. More recent physiological experiments have revealed that, in a healthy cochlea, the maximum is displaced gradually toward the cochlear base (input) as the sound pressure is increased, whereas the pitch remains practically constant. This paradox suggests that the maximum excitation may not be the adequate code for the pitch after all. In the presence of hearing loss of cochlear origin, the pitch appears higher than normal. As the sound pressure level is increased, it changes gradually back to normal. By contrast, the maximum of cochlear excitation in the presence of cochlear damage, although displaced toward the cochlear base, remains independent of sound pressure level. In both situations, normal and pathological, the apical cut off of cochlear excitation depends on the sound pressure level in the same way as does the pitch. Could the cut off be the adequate place code for the pitch?